Uso de las tic en el aprendizaje de estudios sociales, en el octavo año de educación general básica, año 2014 - Salazar Morales, Andrea Stéfania (2015)
Technologies of computing and communication technology TIC represent today a transcendental factor in the field of education running as strategies of teaching within specific areas, taking into account the social studies area allows to know the reality in which we are developing our activities, fostering the recognition as a social media entities. The research has been done to all teachers of the school of basic education Provincial Council of Cotopaxi and the eighth year on the subject of social studies students to know the degree of influence and the advantages provided by the use of TIC to strengthen the skills within the indicated subject. TIC at the present time are an essential tool for the professional, technical and scientific development.